Deep learning in medical image analysis and multimodal learning for clinical decision support : third International Workshop, DLMIA 2017, and 7th International Workshop, ML-CDS 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, Proceedings /: third International Workshop, DLMIA 2017, and 7th International Workshop, ML-CDS 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, Proceedings. (2017) - Unknown
No abstract available